3(x+1)+2x=3(3x+1)

Simple and best practice solution for 3(x+1)+2x=3(3x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)+2x=3(3x+1) equation:



3(x+1)+2x=3(3x+1)
We move all terms to the left:
3(x+1)+2x-(3(3x+1))=0
We add all the numbers together, and all the variables
2x+3(x+1)-(3(3x+1))=0
We multiply parentheses
2x+3x-(3(3x+1))+3=0
We calculate terms in parentheses: -(3(3x+1)), so:
3(3x+1)
We multiply parentheses
9x+3
Back to the equation:
-(9x+3)
We add all the numbers together, and all the variables
5x-(9x+3)+3=0
We get rid of parentheses
5x-9x-3+3=0
We add all the numbers together, and all the variables
-4x=0
x=0/-4
x=0

See similar equations:

| 3(4x-1)=9-x=2x+8+9x | | 3.1x-2.5=4.2x+0.52 | | 3h+24=7h-12 | | 9x/x+1=2-9/x+1 | | 7(x+1))=2x+57 | | 12=2x+17 | | 6(-2y)+y=22 | | -2v+2=8 | | -9=2m+3+2m | | 6x-4=-2x-9 | | 2-3(b+1)=2b | | n+51/4=12/3 | | 9(900-10y÷3)+8y=1116 | | 4.2+1.8=2.5a | | -3(4-3k)=5k+16 | | 13=c/3+4 | | -34=-7u+2(u-7) | | 3y+2=114 | | X=900-10y | | 5x+22=3x-4+6x+2 | | -4=2(x+6)-4x | | 2|x+13|+4=10 | | 5y-35=2y+20 | | 13m-4(2m-5)=-10 | | 1/2x+6=-(2x+8)-x | | -2x+3=30+x | | 8+12=-5(7x-4) | | -7w+2(w-3)=-31 | | 2x+1=-(4x+-7) | | 16-3a=-6a+9 | | -5x+17=7x-9 | | x5−6+9=1 |

Equations solver categories